Tourism Area Life Cycle Analysis in the Development of Aan Tourism Village, Klungkung - Yusnny, Bella Desita; Sena, I Made Aswin Ananta (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This study aims to analyze the development of Aan Tourism Village in Klungkung Regency, Bali, using the Tourism Area Life Cycle (TALC) approach from Butler (1980). Research methods: A qualitative descriptive approach was used with direct observation techniques and in-depth interviews with key informants to understand the dynamics of tourism that occur. Findings: Aan Village is in a transition period from the development stage to consolidation. This is indicated by an increase in the number of tourist visits, community involvement in tourism activities, development of supporting infrastructure, and the implementation of formal regulations. However, several challenges have begun to emerge, such as uneven community involvement and expectations of economic benefits that have not been fully achieved. Implication: Strategies for strengthening institutions, tourism product innovation, and increasing digital promotion are recommended to encourage sustainability. These findings contribute to the formulation of sustainable tourism village development policies that are oriented towards a balance between economic, social, and environmental aspects.